A Suggested Role of Human Growth Hormone in Control of the COVID-19 Pandemic - Elkarow, Mohamed Hamdy; Hamdy, Amr (Frontiers in Endocrinology, 2020)
Covid19 is a worldwide pandemic challenge that started in Wuhan- China and spread to almost all countries on the planet within a few months. The causative virus was found to be highly contagious and until now considerably difficult to contain. A look at the epidemiological distribution of the disease over the planet has raised a number of questions whose answers could help us understand the behavior of the virus and consequently leads us to possible means of limitation of its spread or even flattening of the curve of morbidity and mortality. After the third decade of life, there is a progressive decline of growth hormone (GH) secretion by approximately 15% for every decade of adult life. The data from highly affected countries suggest a more aggressive course in the elderly, a double-time affection of males more than females, and the vulnerability of some risk groups of patients. Our observation is that GH deficiency is a common factor in all vulnerable patient groups. We think that there is a need for studying the role of growth hormone in the unique epidemiological pattern of Covid-19 so that it might help in the early detection and management of the high-risk groups as appropriate.